Bibliographic reviews as an element of similarity between journals. Analysis of the category Communication in Web of Science - Repiso, Rafael; de Aguilera, Miguel; Castillo Esparcia, Antonio (Revista General de Información y Documentación, 2019)
This paper analyses the Book Reviews published in Communication journals indexed in thecategory Social Science Citation Index (WoS) in the period 2013-2017. Through the co-presence ofthe same works reviewed in different journals, the aim is to study the relationship of similaritybetween journals in the area. The results show how 25 journals do not publish reviews, analyzing 63journals, which allows to study the individual similarity of journals and at the same time generate areamaps. The methodological proposal is valid but limited. The results in the area of Communication arelogical, grouping the journals by defined topics. Using bibliographic reviews as an element ofsimilarity between journals should in any case be complementary to other methods and will beespecially significant in areas of Humanities, where books are the object of study.
Keywords: Bibliographic Reviews; journals; Communication Journals; Maps of Journals; Journals; Cluster of Journals